New insights into the morphology and taxonomy of the Cretaceous conifer Frenelopsis based on a new species from the Albian of San Just, Teruel, Spain. (March 2019) - Barral, Abel; Gomez, Bernard; Daviero-Gomez, Véronique; Lécuyer, Christophe; Mendes, Mário Miguel; Ewin, Timothy A.M.
Abstract: Frenelopsis justae sp. nov. is reported from the middle – lower upper Albian Escucha Formation of San Just, Teruel province, Spain. It shows micro-morphological features hitherto undescribed in the genus Frenelopsis including: (1) individual stomatal apparatus comprised of only three subsidiary cells; (2) clusters of 2–3 stomatal apparatus sharing a single subsidiary cell; (3) stomatal rows that bifurcate; and (4) an internal, cylindrical, cell layer preserved between the adaxial and abaxial cuticles. The morphology in the genus is reinterpreted, the long leaf sheath consisting of the proximal abaxial surface of 2–3 fused leaves lacking visible sutures with short distal free parts. Therefore, the generic diagnosis is emended, and new microscopic features added. We show that the appearance, morphology and structure of the leaf surfaces, free leaf tips, and stomatal apparatus are highly variable and regard them as innovation hot-spots in Frenelopsis species. We emphasize the need to perform thorough quantitative analysis of Frenelopsis morphology, including description of metrics variance, to improve our knowledge of its taxonomy, phenotypical plasticity and evolutionary trends. Highlights: The new species Frenelopsis justae is described. Stomatal apparatus of 3 subsidiary cells are firstly described for Frenelopsis. The leafy stem morphology of the genus is reinterpreted. Emendation of the genus diagnosis is provided. Free leaf tips, stomata and leaf surface are variability hot-spots in Frenelopsis.